Votán-Zapata contra a Besta-fera: escritos do EZLN contra o capitalismo no México - Anjos, Diego Marques Pereira dos [UNESP] (2014)
The present master thesis has the object to study, the declarations of the Zapatista Army of National Liberation (EZLN), a Mexican political movement. Do we seek to understand the meaning of textual production of the EZLN through a selected set of texts in which the organization presents his world vision, his way of organization, the critique of capitalist society, their objectives.Our methodology had as its starting point the idea that to understand and explain a speech is necessary to discover the social conditions of production of discourse, and the work that follows is a presentation of the external motivations and of internal unity of the EZLN discourse. In the third part of our work, do we seek realize a critical reflection on the announcements by EZLN based on the concepts of ideology and utopia, and as a result of our reflection, we indicate that the EZLN presents a critical discourse on Mexican society, but don't develop a alternative and radical project of social transformation.